Assessment of Chelators in Wort and Beer Model Solutions - Mertens, Tuur; Kunz, Thomas; Methner, Frank-Jürgen (BrewingScience, 2020)
Long-term storage of beer often results in flavour deterioration and quality reduction. Prolonging beer freshness would benefit both brewers and consumers worldwide. Oxygen has always been a major focus in regard to oxidation. Less naturally is the key involvement of catalytic transition metals (Fe, Cu, Mn) in oxidative beer ageing. Physicochemically removing these entities through chelation - rendering them incapable of forming reactive oxygen species - could greatly benefit flavour stability. This study aims to explore nine chelating compounds (EDTA, citric acid, tartaric acid, quercetin, chlorogenic acid, ferulic acid, gallic acid, phytic acid, and tannic acid) for their capacity to form complexes with seven metal ions (FeII, FeIII, CuII, MnII, CaII, ZnII, MgII) and to examine whether the complexes can effectively be removed by filtration. Chelators and metal ions were mixed and incubated in two distinct acetate buffer solutions, one with the pH and ethanol content of wort (5.60; 0.0 vol%) and one with that of finished beer (4.30; 5.0 vol%). Measurements were conducted by UV-Vis and ICP-OES spectroscopy, to respectively assess complex formation (through absorbance changes) and filterability (through metal level reductions). Ideally, chelators deplete iron, copper, and manganese, without affecting any metals vital for brewing (Ca, Zn, Mg). The findings suggest tannic acid to be the most promising chelator in this aspect, followed by quercetin, gallic acid, chlorogenic acid, and ferulic acid. EDTA, citric acid and tartaric acid did not form filterable complexes with any of the metal ions. Phytic acid chelated out zinc; among others when introduced to a mix of metal ions. Compared to beer pH, wort pH proved far superior overall in terms of transition metal removal by complex formation.